Między biedermeierem a grozą Holocaustu. Filmowa reprezentacja perspektywy nekrofila w Palaczu zwłok Juraja Herza - Birkholc , Robert (Załącznik Kulturoznawczy, 2018)
This article provides in-depth analysis and interpretation of The Cremator (1969), the Czechoslovak film, which, in the opinion of the author, is one of the most interesting movies with subjective narration. While describing the narration of the film, the author introduces the category of a “mediated subjectivisation”. This figure of subjectivisation is not a direct presentation of what the character sees or thinks but it is rather a kind of variation about the protagonist’s mental states. All events and characters in The Cremator are shown from the perspective of Karl Kopfrkingl, a man who adores everything that is dead. The author analyzes how the director of the movie Juraj Herz made an audiovisual representation of the necrophilic desires. Irony is that Kopfrkingl looks like a typical “Biedermeier man” and perceives himself as an ideal father and husband. However, his necrophilic desires cause him to cooperate with the Nazis and murder his family. Various filmThis article provides in-depth analysis and interpretation of The Cremator (1969), the Czechoslovak film, which, in the opinion of the author, is one of the most interesting movies with subjective narration. While describing the narration of the film, the author introduces the category of a “mediated subjectivisation”. This figure of subjectivisation is not a direct presentation of what the character sees or thinks but it is rather a kind of variation about the protagonist’s mental states. All events and characters in The Cremator are shown from the perspective of Karl Kopfrkingl, a man who adores everything that is dead. The author analyzes how the director of the movie Juraj Herz made an audiovisual representation of the necrophilic desires. Irony is that Kopfrkingl looks like a typical “Biedermeier man” and perceives himself as an ideal father and husband. However, his necrophilic desires cause him to cooperate with the Nazis and murder his family. Various film techniques, such as framing and editing, metaphorically shows split personality of the main character. The creators of the movie suggest that the man’s dark inclinations have their sources in a lifeless culture of Biedermeier. As the author argues, mediated subjectivisation in The Cremator captures deep feelings of the character while simultaneously enabling the viewer to keep a distance from him, for instance, by ironically exaggerating some features of the character’s perception of the world.